2016
DOI: 10.1097/aln.0000000000001213
|View full text |Cite
|
Sign up to set email alerts
|

α2-Adrenergic Receptor and Isoflurane Modulation of Presynaptic Ca2+ Influx and Exocytosis in Hippocampal Neurons

Abstract: Background Evidence indicates that the anesthetic-sparing effects of α2-adrenergic receptor (AR) agonists involve α2A-AR heteroreceptors on nonadrenergic neurons. Since volatile anesthetics inhibit neurotransmitter release by reducing synaptic vesicle (SV) exocytosis, the authors hypothesized that α2-AR agonists inhibit nonadrenergic SV exocytosis and thereby potentiate presynaptic inhibition of exocytosis by isoflurane. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 53 publications
(101 reference statements)
3
16
0
Order By: Relevance
“…The effect of mesedin on the cholinergic activity and synaptic formation and maturation via an increase in ChAT and PSD95 expression may be at least partially explained by the α2 blockade induced increase of neural growth factor, that in turn is capable of enhancing ChAT and PSD95 production [ 54 , 55 ]. The α2 blockade by mesedin appears also to increase the expression of the pre-synaptic marker of exocytosis, synaptophysin, in neurons, and astroglia from 3×Tg-AD APC, which is logically concordant with the notion that α2 agonists are involved in inhibition of synaptic vesicle exocytosis in hippocampal neurons [ 56 ]. Taking into account the synaptogenic function of astrocytes [ 57 ], it can be suggested that α2 blockade by mesedin provides the improvement of this function, acting (i) directly via its synaptophysin/PSD95-increasing effect on the neurons, and (ii) indirectly through the protection of astrocytes against hypoxia and Aβ cytotoxicity.…”
Section: Discussionsupporting
confidence: 57%
“…The effect of mesedin on the cholinergic activity and synaptic formation and maturation via an increase in ChAT and PSD95 expression may be at least partially explained by the α2 blockade induced increase of neural growth factor, that in turn is capable of enhancing ChAT and PSD95 production [ 54 , 55 ]. The α2 blockade by mesedin appears also to increase the expression of the pre-synaptic marker of exocytosis, synaptophysin, in neurons, and astroglia from 3×Tg-AD APC, which is logically concordant with the notion that α2 agonists are involved in inhibition of synaptic vesicle exocytosis in hippocampal neurons [ 56 ]. Taking into account the synaptogenic function of astrocytes [ 57 ], it can be suggested that α2 blockade by mesedin provides the improvement of this function, acting (i) directly via its synaptophysin/PSD95-increasing effect on the neurons, and (ii) indirectly through the protection of astrocytes against hypoxia and Aβ cytotoxicity.…”
Section: Discussionsupporting
confidence: 57%
“…It is well known that Dex is a highly selective α 2 adrenergic receptor agonist. Therefore, we used Atip, an α 2 adrenergic receptor antagonist, to determine whether the protective effect of Dex on TBI-induced ALI in mice was related to its α 2 adrenergic receptor activating effect [ 31 ]. Results showed that Atip partly reversed serum HMGB1 levels and the expression of RAGE in lung tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Being mostly G i -coupled, α2 adrenergic receptor activation is generally inhibitory, reducing cAMP synthesis, and causing opening of K + channels or inhibition of AMPA glutamate-gated channels (Aghajanian and VanderMaelen, 1982 ; Franks, 2008 ; Ishii et al, 2008 ; Lur and Higley, 2015 ). Most often, the α2 receptor class is found on neuronal terminals, including noradrenergic LC axons, but also on many other types of neuron, and acts to reduce transmitter release (Matsuo et al, 2003 ; Shields et al, 2009 ; Hara et al, 2016 ). The prototype drug clonidine also produces sedation and works through these α2 adrenergic receptors, but activates other types of metabotropic receptor too.…”
Section: The α2 Adrenergic Sedatives Dexmedetomidine Guanfacine and mentioning
confidence: 99%